2001
DOI: 10.1523/jneurosci.21-23-09204.2001
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of cAMP Response Element-Binding Protein in Hippocampal Neurons as a Protective Response after Exposure to GlutamateIn Vitroand IschemiaIn Vivo

Abstract: Although accumulating evidence indicates that cAMP response element-binding protein (CREB) phosphorylation mediates not only synaptic plasticity but also survival of certain neurons, it remains uncertain whether CREB phosphorylation induced after metabolic insult leads to CRE-mediated gene transcription and is involved in cell survival or not. In the present study, we clarified that (1) CREB phosphorylation and ischemic tolerance induced after preconditioning ischemia in the hippocampal neurons was abolished b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
221
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(232 citation statements)
references
References 44 publications
9
221
1
1
Order By: Relevance
“…The Effect of Chronic Stress on pCREB Staining. As reported (23), CREB phosphorylation reflects elevated glutamatergic activity in the hippocampus. There was a significant effect of experi- Post hoc analysis using a Newman-Keuls test indicates that stressed animals had a significantly higher density of pCREB staining than controls in the CA3 (P Ļ½ 0.01) and DG (P Ļ½ 0.01).…”
Section: The Effect Of Chronic Stress and Lithium Treatment On Ca3 Pysupporting
confidence: 56%
See 1 more Smart Citation
“…The Effect of Chronic Stress on pCREB Staining. As reported (23), CREB phosphorylation reflects elevated glutamatergic activity in the hippocampus. There was a significant effect of experi- Post hoc analysis using a Newman-Keuls test indicates that stressed animals had a significantly higher density of pCREB staining than controls in the CA3 (P Ļ½ 0.01) and DG (P Ļ½ 0.01).…”
Section: The Effect Of Chronic Stress and Lithium Treatment On Ca3 Pysupporting
confidence: 56%
“…The dendritic shrinkage in CA3 pyramidal cell neurons after CRS can be blocked by treatment with the anticonvulsant drug, phenytoin, and the antidepressant tianeptine, both of which have been shown to block excitotoxicity (20)(21)(22). In addition, excitotoxic increases in glutamate lead to phosphorylation of cAMP-response element binding (CREB) (23). Moreover, the transcription factor CREB is implicated in stress effects and the pathology of MDD (24), and CREB protein mRNA levels are increased by chronic antidepressant treatment (25).…”
mentioning
confidence: 99%
“…Indeed, it has been reported that inhibiting the phosphorylation of CREB increases the degree of neuronal injury following insult (Mabuchi et al, 2001). Conformably, RD rats that underwent exercise training performed superlatively on the MWM task, probably by a dynamic utilization of phospho-CREB based on the depletion of total-CREB and inverted correlation between the two.…”
Section: The Role Of Bdnf On the Restorative Effects Of Exercise Counmentioning
confidence: 98%
“…Indeed, brief stimulation of NMDA receptors in vivo, such as during transient ischemia (Mabuchi et al 2001) or tetanic stimulation of corticostriatal pathways (Charpier and Deniau 1997) was able to trigger persistent biochemical and functional effects, such as CREB phosphorylation and LTP, respectively.…”
Section: )mentioning
confidence: 99%